Performance of four ischemic stroke prognostic scores in a Brazilian population - Gustavo W. Kuster; Lívia A. Dutra; Israel P. Brasil; Evelyn P. Pacheco; Márcio J. C. Arruda; Cristiane Volcov; Renan B. Domingues (Arquivos de Neuro-Psiquiatria)
ABSTRACT Objective Ischemic stroke (IS) prognostic scales may help clinicians in their clinical decisions. This study aimed to assess the performance of four IS prognostic scales in a Brazilian population. Method We evaluated data of IS patients admitted at Hospital Paulistano, a Joint Commission International certified primary stroke center. In-hospital mortality and modified Rankin score at discharge were defined as the outcome measures. The performance of National Institutes of Health Stroke Scale (NIHSS), Stroke Prognostication Using Age and NIHSS (SPAN-100), Acute Stroke Registry and Analysis of Lausanne (ASTRAL), and Totaled Health Risks in Vascular Events (THRIVE) were compared. Results Two hundred six patients with a mean ± SD age of 67.58 ± 15.5 years, being 55.3% male, were included. The four scales were significantly and independently associated functional outcome. Only THRIVE was associated with in-hospital mortality. With area under the curve THRIVE and NIHSS were the scales with better performance for functional outcome and THRIVE had the best performance for mortality. Conclusion THRIVE showed the best performance among the four scales, being the only associated with in-hospital mortality.